The effectiveness of primary care streaming in emergency departments on decision-making and patient flow and safety – A realist evaluation. (May 2022) - Edwards, Michelle; Cooper, Alison; Hughes, Thomas; Davies, Freya; Price, Delyth; Anderson, Pippa; Evans, Bridie; Carson-Stevens, Andrew; Dale, Jeremy; Hibbert, Peter; Harrington, Barbara; Hepburn, Julie; et al.
Abstract: Primary care streaming was implemented in UK Emergency Departments (EDs) to manage an increasing demand for urgent care. We aimed to explore its effectiveness in EDs with different primary care models and identify contexts and mechanisms that influenced outcomes: streaming patients to the most appropriate clinician or service, ED flow and patient safety. Method: We observed streaming and interviewed ED and primary care staff during case study visits to 10 EDs in England. We used realist methodology, synthesising a middle-range theory with our qualitative data to refine and create a set of theories that explain relationships between contexts, mechanisms and outcomes. Results: Mechanisms contributing to the effectiveness of primary care streaming were: quality of decision-making, patient flow, redeploying staff, managing patients across streams, the implementation of governance protocols, guidance, training, service evaluation and quality improvement efforts. Experienced nurses and good teamworking and strategic and operational management were key contextual factors. Conclusion: We recommend service improvement strategies, operational management, monitoring, evaluation and training to ensure that ED nurses stream patients presenting at an ED seeking urgent care to the most appropriate clinicians for their needs in a safe and efficient manner.